The Influence of Indonesian Interest Rates, Inflation, Debt to Asset Ratio and Return on Asset against the Property and Real Estate Sector Stock Prices on the Indonesia Stock Exchange in 2014-2018 - Yeni Ariesa; Agung Sahbana; Prabowo Chuanda; Cindy Angela Kirana; Ervia Florencia Livinda; Wira Wijaya (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The aim of this study is to see the effect of Indonesia's interest rates, inflation, DAR and ROA on stock prices. This type of research is quantitative research, uses a deductive approach and is descriptive in nature. The population of the property and real estate sector has 52 companies, within 5 years, so the data totaled 155.          The results of this study show that simultaneously SBI, inflation, DAR and ROA have a significant effect on stock prices. Partially, only ROA has a positive / significant effect on the stock price. Other variables, namely SBI, inflation and DAR do not affect the stock price. The amount of stock price variation that can be explained by the independent variable used is 18.3%, the remaining 81.7% is influenced by other variables.